FEMALE RIGHTS DURING LABOR AND THE PUERPERIUM - Petricio Martins, Karoline; Martins de Marco Santos, Enzo; de Matos Sales, Letícia; Machado, Elizeu; Andressa Lopes e Vasconcelos, Cícera; da Rocha Nascimento Pereira, Rosenilda; Aparecida de Souza Cardoso, Dalva; de Jesus Machado Mariot, Elizilda; Aparecida de Franca dos Santos, Regiane; Maria Príncipe Crucinsky, Viviane (Health and Society, 2024)
Professional assistance provided to women during childbirth and the postpartum period has undergone changes over the years, with the aim of guaranteeing the rights of these women. Therefore, the general objective of this study is to analyze women’s rights during labor and the postpartum period. To this end, a narrative review was carried out, using articles from the VHL, PubMed and SciELO databases, which were published between 2014 and 2024. Three categories were developed to compose this study, namely: Health education as a way of guaranteeing rights, the importance of humanized birth as a pregnant woman’s right and women’s option for cesarean sections. It is noted that guaranteeing women’s rights is fundamental at the time of childbirth and the postpartum period, but the humanization and guarantee of these rights is still considered a challenge for their insertion.